The ‘Hero Gigi’ Project: The Use of Teledentistry to Empower Aboriginal Community - Abang Abdullah, Asma Alhusna; Jaafar, Azlan (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: The ‘Hero Gigi’ project aimed to empower 5-6-year-old children in Tabika KEMAS of Kampung Orang Asli Ulu Lakai, an Aboriginal community in Negeri Sembilan. The children were taught to take charge of their dental health through a teacher-led intervention. Methods: The project was started by employing a teledentistry approach, utilizing online teaching to impart oral health care knowledge to the teacher. Face-to-face demonstrations were conducted to provide practical training on toothbrushing. The teacher was provided with the ‘Hero Gigi’ teaching module which was designed specifically for Aboriginal children, contained a teaching module, storybook, flashcards, and an activity book. Subsequently, five students were chosen as the'HERO GIGI' and received training from the teacher using the provided module. The 'HERO GIGI' were then entrusted to share their knowledge with their peers using flashcards and conduct toothbrushing demonstration. Pre- and post-intervention oralhygiene assessments were conducted among the 14 children to evaluate the effectiveness of this project. Results: The results indicated that 71% of the children had reduction in plaque score, signifying an improvement in their oral hygiene. Conclusion: By leveraging technology to disseminate knowledge and utilizing student leaders to cascade information, this ‘Hero Gigi’ project not only enhanced dental health but also fostered a sense of responsibility and leadership among the young participants. The findings of this project hold promise for a similar intervention in other communities to promote dental health and overall well-being among children. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S42